STRATEGI PENGEMBANGAN HOMESTAY BERBASIS 9PS MARKETING MIX: STUDI KASUS DESA WISATA DARUNU - Letunaung, Geraldy; Sambeka, Vesty Like; Takaendengan, Mita E (HOSPITALITI DAN PARIWISATA, 2025)
This study aims to formulate a homestay development strategy based in Darunu Tourism Village, WoriSubdistrict, North Minahasa Regency, North Sulawesi. Homestays play a crucial role in enhancingtourist comfort due to their proximity to major attractions, such as the mangrove area. Their presenceenables visitors to stay longer, which helps circulate income in the local economy through services likelodging, breakfast, local transportation, and traditional snacks provided by residents. Homestays alsofunction as a means of empowering the community, particularly by utilizing local houses that arepotential to be developed into homestays. Promotion of homestays is conducted in conjunction with thepromotion of tourist attractions, creating a mutually reinforcing impact and the more guests stay inhomestays, the higher the potential visits to the tourism objects. This research employs a qualitativemethod with data collected through observation, interviews, and documentation. The analysis is basedon the nine elements of the 9Ps Marketing Mix: Product, Price, Place, Promotion, People, Process,Physical Evidence, Partnership, and Participation. The results show that homestay development inDarunu is not yet optimal in several aspects, especially in terms of promotion and facilities. However,the increase in the number of homestays from one to four reflects positive growth potential if supportedby the right strategy